Genetic and environmental associations between body dissatisfaction, weight preoccupation, and binge eating: Evidence for a common factor with differential loadings across symptom type. Issue 2 (16th September 2016) - O'Connor, Shannon M.; Beam, Christopher R.; Luo, Xiaochen; Cohen, L. Adelyn; VanHuysse, Jessica L.; Emery, Robert E.; Turkheimer, Eric; Keel, Pamela K.; Burt, S. Alexandra; Neale, Michael; Boker, Steven; Klump, Kelly
ABSTRACT: Objective: Prior twin studies provide support for a single "common factor" that contributes genetic and environmental risk to a range of disordered eating symptoms. However, the common factor may be indexed less well by binge eating (BE) than other symptoms of eating disorders [i.e., body dissatisfaction (BD) and weight preoccupation (WP)]. We sought to explore the presence of a common factor and test whether loadings differed across three key symptoms (i.e., BE, BD, WP). Method: Disordered eating was assessed via self‐report in 631 female twin pairs from the Michigan State University Twin Registry. Results: We detected a common disordered eating factor that was influenced primarily by additive genetic and nonshared environmental influences. However, we observed different loadings on this common factor by symptom type, as factor loadings for BD and WP were stronger than that for BE. Moreover, the residual environmental and/or genetic variances (i.e., those that are independent of the common factor) were larger in BE than those of BD or WP. Discussion: Although all three symptoms share a common set of genetic and environmental influences, risk for BE may involve additional genetic, biological, and environmental factors that are not shared with other symptoms of eating pathology. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2017; 50:157–161)